Kemampuan Ekstrak Kulit Buah Kabau (Archidendron microcarpum) dalam Mengendalikan Crocidolomia pavonana (Lepidoptera: Crambidae): Ability of Kabau Fruit Crude Extract (Archidendron microcarpum) in Controlling Crocidolomia pavonana (Lepidoptera: Crambidae - Obel, Obel; Apriyanto, Dwinardi; Pamekas, Tunjung (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2020)
Crocidolomia pavonana Fabricius is an important pest in the Brassicaceae family that can cause up to 10% -100% yield losses. One of the plants that are considered as potential botanical insecticides is Kabau Plant (Archidendron microcarpum (Benth.). This study was aimed to determine the ability of kabau pell crude extract to control C.pavonana. The study was conducted at Rejang Lebong State Community Academy Campus and Natural Resources Organic Laboratory of Faculty of Mathematics and Natural Sciences, Universitas Andalas, from September 2016 to February 2017. The research was conducted in three stages: filter, bioactivity, and chemical profile examination. The results showed that the kabau peel crude extract was classified as an active insecticide for C.pavonana. At a concentration of 0.5%, kabau peel crude extract caused larval mortality to reach 63.33% in the filter test and 70% in the bioactivity test. The extract consisted of phenolic compounds, saponins, flavonoids, steroids, terpenoids, and alkaloids. Keywords: Kabau plant, secondary metabolite, botanical insecticide, Crocidolomi pavonana